First report of stem blight caused by Diaporthe eres on highbush blueberry (Vaccinium corymbosum) in Michigan - Klein-Gordon, Jeannie M (Plant disease, 2023)
The U.S. is the world's leading producer of highbush blueberries (Vaccinium corymbosum L.), and Michigan is ranked in the top five production states (USDA NASS, 2022). In June and July of 2021, 268 blueberry stem blight samples were collected for a pathogen survey across 22 total fields in Van Buren and Ottawa counties in Michigan. Current season stems with symptoms of necrosis and wilting were collected. Stems were cut just below the necrotic area and cross-sections (2-3 mm long) were surface disinfested in 10% bleach for 1 min, rinsed twice in sterile distilled water, and dried on sterile paper towels. Stem cross-sections were plated onto potato dextrose agar (PDA) amended with 100 µg/ml streptomycin sulfate and 50 µg/ml ampicillin. Plates were incubated at 21°C under a 12-h photoperiod for 5-6 days. Outgrowing fungi with morphology similar to Diaporthe spp. were transferred to new PDA plates 2 consecutive times after 7 days of similar incubation to ensure single colony isolation. After 7 days, colonies consisted of white and light brown mycelia that were mostly flat, with some isolates that had partially raised mycelia towards the center of the plate. After 3-4 weeks, colonies turned brown and gray and produced dark brown pycnidia. Aseptate, hyaline, fusiform to ellipsoid, biguttulate alpha conidia measuring 5.4 to 7.6 x 2.6 to 3.7 µm (n = 60) were produced. No beta conidia were observed. In total, 3 isolates, representing 3 different farms (37-95 km apart) and cultivars ('Duke', 'Jersey', and 'Bluecrop'), as well as 2 counties, were identified as Diaporthe through colony morphology (Gomes et al. 2013, Udayanga et al. 2014). Amplification and subsequent Sanger sequencing were performed for the internal transcribed spacer (ITS) region and portions of the translation elongation factor (TEF) 1-α, β-tubulin (TUB), and histone H3 (HIS) genes using primers ITS5/ITS4 (White et al. 1990), EF1-728F/EF1-986R (Carbone and Kohn 1999), T1/Bt-2b (Glass and Donaldson 1995), and CYLH3F/H3-1b (Glass and Donaldson 1995), respectively. Representative sequences were deposited in NCBI GenBank (accession no. OQ507870-OQ507872 for ITS, and OQ550272-OQ550278 for TEF, HIS, and TUB). BLASTn results revealed 97-100% identity for all 4 genes across other established D. eres isolates reported in Gomes et al. (2013). For example, JMK047 had 99.8% (577/578 bp), 99.7% (327/328 bp), 100% (701/701 bp), and 100% (439/439 bp) homology with ITS, TEF, TUB, and HIS sequences, respectively, of D. eres CBS 439.82 (accession no. KC343090, KC343816, KC344058, KC343574). Koch's Postulates were fulfilled via pathogenicity tests on 2-year-old potted 'Blueray' plants with 2 isolates. Stems were surface sterilized with 1% bleach then 8-mm long pieces of bark were removed using a sterile razor blade to expose the cambium. Plugs of sterile PDA (negative control) or mycelia from 7-day old cultures on PDA (5-mm diameter) were placed onto the cambium layer and sealed with Parafilm. Six stems on unique plants were inoculated per treatment. Plants were grown in a 20.5°C greenhouse with a 14-hr photoperiod. After 3 weeks, the stems inoculated with D. eres isolates showed similar stem blight symptoms to those observed in the field while control stems remained healthy. Re-isolation and sequencing of the ITS region of 3 replicates per treatment with the protocol described above confirmed symptoms correlated with D. eres isolates. This is the first report of D. eres associated with stem blight of highbush blueberry in Michigan, and the second report in the U.S. (Lombard et al. 2014). Increasing prevalence of D. eres in U.S. blueberries may affect disease management programs. References Carbone, I., and Kohn, L. M. 1999. Mycologia 91:553. 10.1080/00275514.1999.12061051. Glass, N. L., and Donaldson, G. C. 1995. Appl. Environ. Microbiol. 61:1323. 10.1128/aem.61.4.1323-1330.1995. Gomes, R. R., et al. 2013. Persoonia 31:1. 10.3767/003158513x666844. Lombard, L., et al. 2014. Phytopathol. Mediterr. 51(2):287. 10.14601/Phytopathol_Mediterr-14034. Udayanga, D., Castlebury, L. A., Rossman, A. Y., Chukeatirote, E., and Hyde, K. D. 2014. Fungal Divers. 67:203-229. 10.1007/s13225-014-0297-2. USDA NASS. 2022. Noncitrus Fruits and Nuts 2021 Summary. White, T. J., et al. 1990. Page 315 in: PCR Protocols: A Guide to Methods and Applications. Academic Press, Inc., San Diego, California, USA